Capitalism and conservation - Brockington, Daniel; Duffy, Rosaleen; Wiley InterScience (Online service) (Malden, MA : Wiley-Blackwell, 2011)
"Through a series of case studies from around the world, Capitalism and Conservation presents a critique of conservation's role as a central driver of global capitalism. Features innovative new research on case studies on the connections between capitalism and conservation drawn from all over the world Examines some of our most popular leisure pursuits and consumption habits to uncover the ways they drive and deepen global capitalism Reveals the increase in intensity and variety of forms of capitalist conservation throughout the world"--
"Many popular leisure pursuits and consumption habits drive and deepen global capitalism - from whale watching in the Azores to sipping an ethically-sourced cup of morning coffee. But what are the consequences for society, nature, and conservation? Capitalism and Conservation presents an important critique of conservation's role as a central driver of global capitalism. This thought-provoking collection of case studies from around the world vividly demonstrates the increase in intensity and variety of forms of capitalist conservation. They also reveal a surprising shift in the conservation movement's own conception of these practices: their current mainstream view is the idea that capitalism can and should help conservation save the world. By examining the works of various corporate billionaires, powerful political coalitions and foundations, international elites and NGOs, and new tourist and business opportunities, the essays show that conservation and capitalism have intertwined to distribute fortune and misfortune in many new ways - with entirely new dynamics of profit creation and marginalisation. Capitalism and Conservation offers illuminating insights and critique of the realities and tensions of capitalism and conservation's coexistence in today's world"--
Front Matter -- Introduction: Capitalism and Conservation: The Production and Reproduction of Biodiversity Conservation / Dan Brockington, Rosaleen Duffy -- A Spectacular Eco-Tour around the Historic Bloc: Theorising the Convergence of Biodiversity Conservation and Capitalist Expansion / Jim Igoe, Katja Neves, Dan Brockington -- The Devil is in the (Bio)diversity: Private Sector b3(BEngagementb4 (Band the Restructuring of Biodiversity Conservation / Kenneth Iain Macdonald -- The Conservationist Mode of Production and Conservation NGOs in sub-Saharan Africa / Dan Brockington, Katherine Scholfield -- Shifting Environmental Governance in a Neoliberal World: US AID for Conservation / Catherine Corson -- Disconnected Nature: The Scaling Up of African Wildlife Foundation and its Impacts on Biodiversity Conservation and Local Livelihoods / Hassanali T Sachedina -- The Rich, the Powerful and the Endangered: Conservation Elites, Networks and the Dominican Republic / George Holmes -- Conservative Philanthropists, Royalty and Business Elites in Nature Conservation in Southern Africa / Marja Spierenburg, Harry Wels -- Protecting the Environment the Natural Way: Ethical Consumption and Commodity Fetishism / James G Carrier -- Making the Market: Specialty Coffee, Generational Pitches, and Papua New Guinea / Paige West -- Cashing in on Cetourism: A Critical Ecological Engagement with Dominant E-NGO Discourses on Whaling, Cetacean Conservation, and Whale Watching / Katja Neves -- Neoliberalising Nature? Elephant-Back Tourism in Thailand and Botswana / Rosaleen Duffy, Lorraine Moore -- The Receiving End of Reform: Everyday Responses to Neoliberalisation in Southeastern Mexico / Peter R Wilshusen -- Index.s
Includes bibliographical references and index.
Print version record.
Keywords: Environmental economics; Conservation of natural resources -- Economic aspects; Consumption (Economics); Capitalism; Capitalism; Conservation of natural resources -- Economic aspects; Consumption (Economics); Environmental economics; Electronic books